Chile - County Gender Assessment : Expanding Women's Work Choices to Enhance Chile's Economic Potential - World Bank (Washington, DC, 2012)
The Chile Country gender assessments (CGAs) identify gender-responsive policies and actions are strategic for poverty reduction, economic growth, human well-being, and development effectiveness. The report proposes priority policy objectives: increase female labor force participation, especially for low-income households, and reduce discontinuity in women's work experience. The report focus on the gender equality in the labor markets; improve access to financial services; expand access to business networks, business development services, and technology for women entrepreneurs. The potential impacts on economic growth gaps of increasing female labor force participation or reducing the gender gap.